1975
DOI: 10.1172/jci108070
|View full text |Cite
|
Sign up to set email alerts
|

Effect of continuous infusion of pentagastrin on lower esophageal sphincter pressure and gastric acid secretion in normal subjects.

Abstract: A B S T R A C T Bolus injections of gastrin or pentagastrin (PG) cause a marked elevation in lower esophageal sphincter pressure (LESP), and it has been suggested that serum gastrin concentration is the main physiological and pathophysiological regulator of LESP. We evaluated this hypothesis by measuring LESP and gastric acid secretion simultaneously in normal subjects during continuous infusion of PG (0.004-12 /Lg/ kg per h), since continuous infusion of a hormone probably simulates physiological hormone rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1976
1976
1989
1989

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The role of gastrin in the physiologic regulation of lower esophageal sphincter pressure (LESP)' is controversial (1)(2)(3)(4)(5)(6)(7)(8). Some observers have proposed that circulating gastrin (3,4) is the major determinant of LESP.…”
Section: Introductionmentioning
confidence: 99%
“…The role of gastrin in the physiologic regulation of lower esophageal sphincter pressure (LESP)' is controversial (1)(2)(3)(4)(5)(6)(7)(8). Some observers have proposed that circulating gastrin (3,4) is the major determinant of LESP.…”
Section: Introductionmentioning
confidence: 99%
“…The demonstrations that human LOS pressure could be modified by gastric infusions of acid and alkali (Castell and Harris, 1970;Beiles et al, 1972;Castell and Levine, 1972;Higgs et al, 1974); that LOS pressure could be consistently increased by gastrin and pentagastrin (Giles et al, 1969;Castell and Harris, 1970;Cohen and Lipshutz, 1971;Lipshutz et al, 1973;Siewert et al, 1974;Trindade et al, 1975); and that LOS pressure in the opossum could be drastically diminished by the use of gastrin antiserum (Lipshutz, et al, 1972) led to the proposal that gastrin was of primary importance in the regulation of LOS pressure. Recent studies, however, have cast considerable doubt upon the physiological relevance of gastrin in this context (Grossman, 1973;Sturdevant and Kun, 1973;Farrell et al, 1974;Goyal and McGuigan, 1975;Walker et al, 1975).…”
mentioning
confidence: 99%
“…Walker et al (1975) reported that there was no statistically significant increase in LES pressure during PG infusion at doses of 0M004-12 ,ug kg-lh-1; however, examination of individual results suggested that PG might be stimulating LES pressure in some subjects and inhibiting it in others. Two further studies Kaye et al, 1976) showed that LES pressure increased during continuous infusion of PG at above maximal ( jig kg-lh-1) or submaximal (09 kg kg-lh-1) doses for gastric acid secretion in man.…”
Section: Discussionmentioning
confidence: 97%
“…This effect has been reported to be enhanced in patients with achalasia (Cohen et al, 1971). Other studies, however, did not confirm these data (Farrell et al, 1974;Sturdevant and Kun, 1974;Goyal and McGuigan, 1976;Walker et al, 1975), and the role of the hormone in maintaining LES tone has yet to be determined.…”
mentioning
confidence: 92%